Legal Consequences of Financing a PT Established by Husband and Wife Without a Marriage Agreement on the Signing of a Lease Agreement - M Madaninabawi; Jawade Hafidz (Sultan Agung Notary Law Review, 2021)
The purpose of this study is to analyze: 1). Regulation of the establishment of a limited liability company by a married couple without a marriage agreement on the signing of a lease agreement in a finance company. 2). The legal consequences of a Limited Liability Company established by a married couple without a marriage agreement are the signing of a lease agreement at a finance company. The research method used in this research is normative juridical research. The data in this study uses secondary data, which is sourced from library materials, while the data analysis uses qualitative analysis. The conclusions in this study are: 1) The regulation of the establishment of a Limited Liability Company by a married couple without a marriage agreement on the signing of a lease agreement in a finance company, namely basically there is no clear statutory regulation regarding the establishment of a Limited Liability Company (PT) by a married couple without a marriage agreement, In practice, it is possible for a Notary to continue serving on the grounds that a PT is an agreement between two or more people and husband and wife as legal subjects have rights and obligations under the law. Even in the establishment of a PT, the Indonesian Ministry of Law and Human Rights - SABH never questioned husband and wife or not, the legal entity of the PT was still ratified. Generally, the lease agreement made is in the standard form made by the lessor, while the lessee only agrees to it. The agreement made is binding on the parties who make it. 2) The legal consequences of a Limited Liability Company established by a married couple without a marriage agreement on the signing of a lease agreement at a finance company, namely the agreement is valid if it fulfills the conditions in the agreement, but in the event of bankruptcy or default in the lease agreement, the liability for the debt or losses to the finance company are not only borne by the assets available in the PT, if the assets in the PT are not sufficient to pay the debts, then husband and wife as well as founders and shareholders will share in the use of the joint assets.